VIRTUDES EPISTÊMICAS E PERFORMANCE NA ESCRITA DE SI DE NELSON WERNECK SODRÉ - MUNIZ JÚNIOR, JOÃO; SILVA, WILTON CARLOS LIMA DA (Outros Tempos: Pesquisa em Foco - História, 2019)
The present study has the purpose of analyzing aspects of the memorialistic writing of the historian, journalist and military Nelson Werneck Sodré, in order to identify narrative choices that reflect on the “epistemic virtues” and the “performance” within an area of expertise, such autobiographical narrative describes not only the individual course, but also some meanders of living experience and academic discipline. Keywords: Epistemic Virtues. Performance. Nelson Werneck Sodré.